Synthetic of pure alumina from aluminum scrap - Abdul Najib Khan, A. Shafiq Khan; Othman, Nur Ezzah Faezah; Purwanto, Hadi; Abdul halim, Hafasihah; Shamsul Baharin, Ahmad Firdaus (Trans Tech Publications, 2015)

(untitled)
Abundance in aluminum scrap metals can cause problem such as limited space allocation and pollution. The solution to solve these problems were by recycling the aluminum scrap metal as secondary production of aluminum. Among the recycling process alternative is smelting, However, the process consumes high energy with low productivity. This study focuses on alumina production from aluminum scrap waste. Dissolution process of Al scrap with 0.5M sodium hydroxide (NaOH) yields Al (OH) 3 and hydrogen gas. Results show that the temperature gradually decreased from 40°C to 35.7°C as the reaction took place. The pH of the solution during dissolution process increased from 12.08 to 12.38. The XRD results show that after calcination of Al (OH)3 powders at 1500°C, α-Al2O3 peaks could be observed. SEM morphology shows that the calcination process changes the Al (OH)3 powders from hexagonal shape to form α-Al2O3 with rounded shape.